An alternative payment on ticket delivered via barcode in M-commerce: a proposed model / Jamil Ya Abdullah - Ya Abdullah, Jamil (2005)
The emerging recent of development in wireless technologies, networking infrastructure, and mobile devices has contributed to the rapid growth of mobile commerce (m-commerce). While e-commerce continues to impact the global business environment, the focus has been directed towards wireless mobile computing. To extend the functionality of e-commerce, one of the best way is to enhance the capability of mobile commerce which is supported by mobile devices. Besides implementation of e-commerce transaction, customer has another alternative to purchase any services that provide by business merchant by using mobile payment. Customer access can be at anytime and at any location. In addition, customer can gain benefits that instantly provide by mobile commerce. Thus, the introduction of a new alternative payment on ticket delivered via barcode proposed model perhaps can bring the alternative solution for mobile ticketing to success. In fact, this model offers benefits to merchant business to enhance the quality of service and enable to develop new platform of profit and revenue in the business. This research paper will discuss about the alternative payment on ticket delivered via barcode model which supported by two elements of payments which are online payment and mobile payment as well. The research includes the proposed model of alternative payment on ticket delivered via barcode, characteristics and the process of existing mobile payment model in local company. Meanwhile, ticket will be sent as a form of barcode via SMS to consumer is new technology in Malaysia that believed will be evolved revolution in Business to Consumer (B2C).